Screening for defects of branched-chain amino acid metabolism - Gibson, K. Michael; Lee, Carol F.; Hoffmann, Georg F. (European journal of pediatrics, 1994)
Screening for defects of branched-chain amino acid metabolism is a sequential process involving clinical evaluation of the patient, plasma carnitine determination, urinary organic acid analysis, and enzyme studies in cultured or isolated peripheral cells. This report will summarize clinical and metabolite features and enzymological methods available for the diagnosis of the more common defects of branchedchain amino acid metabolism, including isovaleryl-CoA dehydrogenase deficiency, 3-methylcrotonyl-CoA carboxylase deficiency, 3-methylglutaconic aciduria due to 3-methylglutaconyl-CoA hydratase deficiency and other less well characterized defects, 3-hydroxy-3-methylglutaryl-CoA lyase deficiency, and 2-methylacetoacetyl-CoA thiolase deficiency. Newer enzymatic methodologies utilizing NaH14CO3 fixation coupled assays are described which allow for the estimation of six enzyme activities in the catabolic pathways ofL-leucine andL-isoleucine catabolism. These coupled assays facilitate the rapid identification of five of the six enzyme abnormalities described above. Their ease of use should allow them to be implemented in any laboratory which screens for inborn errors of metabolism
Gesehen am 28.10.2025